2014
DOI: 10.1038/npp.2014.182
|View full text |Cite
|
Sign up to set email alerts
|

GluN2B-Containing NMDA Receptors Blockade Rescues Bidirectional Synaptic Plasticity in the Bed Nucleus of the Stria Terminalis of Cocaine Self-Administering Rats

Abstract: Drugs of abuse have detrimental effects on homeostatic synaptic plasticity in the motivational brain network. Bidirectional plasticity at excitatory synapses helps keep neural circuits within a functional range to allow for behavioral flexibility. Therefore, impaired bidirectional plasticity of excitatory synapses may contribute to the behavioral hallmarks of addiction, yet this relationship remains unclear. Here we tracked excitatory synaptic strength in the oval bed nucleus of the stria terminalis (ovBNST) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Decreased NMDAR function could contribute to the cortical hypofunction that can promote cocaine seeking, likely by decreasing cortical control over behavioral inhibition and regulation (Chen et al ; McGinty et al ; Murphy et al ). However, systemic GluN2B inhibition does not reduce lever‐pressing for cocaine (deBacker et al ), which might not be predicted if reducing cortical NMDAR function promotes self‐administration. One possibility is that more moderate GluN2B changes (after drug intake) could have different effects relative to more complete GluN2B inhibition (by pharmacological blockers).…”
Section: Nmdar Contributions To Psychostimulant Addictionmentioning
confidence: 99%
See 4 more Smart Citations
“…Decreased NMDAR function could contribute to the cortical hypofunction that can promote cocaine seeking, likely by decreasing cortical control over behavioral inhibition and regulation (Chen et al ; McGinty et al ; Murphy et al ). However, systemic GluN2B inhibition does not reduce lever‐pressing for cocaine (deBacker et al ), which might not be predicted if reducing cortical NMDAR function promotes self‐administration. One possibility is that more moderate GluN2B changes (after drug intake) could have different effects relative to more complete GluN2B inhibition (by pharmacological blockers).…”
Section: Nmdar Contributions To Psychostimulant Addictionmentioning
confidence: 99%
“…Recent studies have identified cocaine‐related NMDAR changes in the bed nucleus of the stria terminalis (BNST), a subcortical region which plays a critical role in anxiety and other emotion‐related behaviors. Cocaine self‐administration increases the decay time of NMDAR currents in BNST, suggesting an increase in GluN2B subunits (deBacker et al ), and also impairs NMDAR‐dependent LTD induction in the BNST. Interestingly, impaired LTD induction could be reversed by blocking GluN2B function, indicating that greater GluN2B function can actually impair some forms of synaptic plasticity.…”
Section: Nmdar Contributions To Psychostimulant Addictionmentioning
confidence: 99%
See 3 more Smart Citations